Highly resolved δ13C and trace element ratios of precisely dated stalagmite from northwestern China: Hydroclimate reconstruction during the last two millennia. (1st September 2022) - Jia, Wei; Zhang, Pingzhong; Zhang, Leilei; Li, Xinhu; Gao, Tao; Wang, Haichuan; Zhang, Haiwei; Li, Hanying; Cheng, Hai; Edwards, R. Lawrence
Abstract: Compared with the widely used stable oxygen isotope (δ 18 O), the climate response of the stable carbon isotope (δ 13 C) of speleothems in monsoonal China has received less attention, mainly because of its relatively complex controlling factors. Nevertheless, an increasing number of studies are suggesting that δ 13 C can represent hydroclimatic changes. Here, we present highly resolved continuous δ 13 C and trace element ratio records of a speleothem from Wanxiang Cave, northwestern China, spanning the last two millennia. Our results show that δ 13 C values oscillated around the mean value on centennial scales, indicating that the overlying vegetation types and soil humidity did not change significantly. High consistency was found between detrended δ 13 C and δ 18 O (δ 13 Cd and δ 18 Od ) records, suggesting that soil moisture balance and vegetation density related to the regional hydrological cycle is an important factor controlling δ 13 C variations on multidecadal-centennial scales. The regional hydrological cycle is mainly controlled by summer precipitation induced by the Asian summer monsoon (ASM) and the stable prior calcite precipitation (PCP), which was inferred from trace element ratio (Mg/Ca, Sr/Ca, Ba/Ca) records. The δ 13 C and trace element ratio records, consistent with δ 18 O throughout the considered periods, are not only closely coupled with the intensity of the El Niño-Southern Oscillation and north-south shift of the Intertropical Convergence Zone but also respond to solar activity and temperature variations in the Northern Hemisphere. However, both δ 13 C and trace element ratios exhibited a persistent significantly decreasing trend in the last 150 years. Furthermore, the variation of δ 18 O during the Current Warm Period (AD. 1850–2000) suggests that anthropogenic emissions of atmospheric CO2 and aerosols rather than ASM caused an unusual increase of regional precipitation and depletion of atmospheric δ 13 C, which induced increased infiltration of atmospheric CO2 and available water into soil pores and caves without any obvious PCP effect. The abnormal changes in our speleothem δ 13 C are analogous to the oceanic 13 C Suess effect, suggesting that stalagmite δ 13 C record is greatly affected by atmospheric CO2 concentration under global warming. Highlights: Speleothem δ 13 C and trace element ratio records from NW China capture precipitation changes related to ASM intensity. Tropical hydrological state, NH temperature, and solar activity are tightly correlated with hydroclimate changes in NW China. The abnormal negative variations in speleothem δ 13 C during the CWP are analogous to the oceanic 13 C Suess effect.